2013
DOI: 10.1080/00140139.2013.771219
|View full text |Cite
|
Sign up to set email alerts
|

Improving target detection in visual search through the augmenting multi-sensory cues

Abstract: This experiment tested 60 individuals on a multiple screen, visual target detection task. Individuals received no-cue augmentation, tactile cue alone, an augmenting auditory cue alone or both of the latter augmentations in combination. Results showed significant and substantive improvements in the combinatorial cueing condition compared with the non-cued control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…This pattern may not hold true for the single task condition where, consistent with prior research (Garcia et al 2012;Hancock et al 2013;Ng and Chan 2012), we expect auditory cues to yield greater accuracy, but tactile cues to yield faster response times.…”
Section: The Present Studysupporting
confidence: 60%
See 1 more Smart Citation
“…This pattern may not hold true for the single task condition where, consistent with prior research (Garcia et al 2012;Hancock et al 2013;Ng and Chan 2012), we expect auditory cues to yield greater accuracy, but tactile cues to yield faster response times.…”
Section: The Present Studysupporting
confidence: 60%
“…For example, Merlo and Hancock (2011) demonstrated a 30% decrease in target response time and a 70% decrease in target identification error rate when using a tactile cueing system. In a follow-up study, Hancock et al (2013) found that performance on a visual search task was significantly faster when participants used either tactile cues or combined audio/tactile cues than either audio cues alone or no cues. Response times in the tactile and audio/tactile cue conditions did not differ from one another.…”
Section: Auditory and Tactile Cueingmentioning
confidence: 98%
“…vibrations presented through a car seat, De Hogema et al, 2009). Potential advantages of multi-sensory warning signals are faster reactions (Bernstein et al, 1969;Diederich and Colonius, 2004;Hershenson, 1962) and reduced risk of sensory overload (Hancock et al, 2013;Lu et al, 2013;Ngo et al, 2012;Prewett et al, 2012;Spence, 2011). However, effective multi-sensory integration requires spatio-temporal and semantic congruency across sensory modalities (Kolers and Brewster, 1985).…”
Section: Toward Multi-modal Warning Signalsmentioning
confidence: 99%
“…The advantage of the multisensory information extends also to paired associative learning in adults [18]. In [26], the authors have shown that multisensory audio/tactile cueing improves the performance (speed and accuracy) of visual search and reduces the amount of mental workload. Promising results were obtained also for children in incidental category learning [9] or numerical learning tasks [31].…”
Section: Unisensory Versus Multisensory Exposure In the Learning Processmentioning
confidence: 99%